Respuesta :

Answer:

a(66) = -10 + 17(65) = 1095

Step-by-step explanation:

We know that this is an arithmetic sequence.  Subtracting -10 from 7 results in 17; subtracting 7 from 24 also results in 17.  Thus, the common difference, d, is 17.  The first term is -10.

The general form of an arithmetic sequence is a(n) = a(1) + d(n - 1).

Substituting -10 for a(1) and 17 for d, we get:

a(n) = -10 + 17(n - 1)

Now let n = 66:  a(66) = -10 + 17(66 - 1), or    a(66) = -10 + 17(65) = 1095

ACCESS MORE